Management of solitary and multiple brain metastases from breast cancer - Addison Willett; J Ben Wilkinson; Chirag Shah; Minesh P Mehta (Indian Journal of Medical and Paediatric Oncology)
As local and systemic control of breast cancer improves, metastasis to the brain remains a common event requiring a specialized management approach. Women diagnosed with breast cancer who develop brain metastases have superior overall survival compared to patients with other forms of metastatic carcinoma. This article summarizes some of the unique aspects of care for patients with breast cancer metastases to the brain.